Perspectives for a music education in the curriculum of arts in basic education: an exploratory study based on the reality of Tocantins - Carlos Alberto Faísca Fernandes Gomes (Universidade Federal do Norte do Tocantins, 2020)
Based on a reading influenced by the professional experience of the author, this study aims to understand the reality experienced in the State of Tocantins with regard to music education, based on an analysis of its state education network, and the municipal education network of its state capital, in a study focused on two distinct axes: the evolution of the curriculum in the state network, between 2013 and 2017, and the reality experienced in the schools of the municipal network of Palmas, Tocantins, as far as music education is concerned. Seeking in this analysis to start from a national view of the curriculum guidelines in the area of music education, the research methodology used is of a qualitative nature, based on observation, document collection, discourse analysis, and the application of a questionnaire to music teachers working in the city of Palmas, Tocantins, during the second half of 2017. In the end, it is concluded that, persisting in the Brazilian reality a dispute between two distinct models of artistic education - one characterized by an integrative approach of different languages, and another by a more autonomous vision that provides curriculum spaces specific to each of these languages -, there is a tendency to regress, namely with the approval of the Common National Curriculum Base, to a more integrative vision of artistic languages, in the wake of the Artistic Education provided by LDB of 1971. It is also noted the state non-compliance with standards and programmatic guidelines for music education at national level.